2021
DOI: 10.5334/jime.677
|View full text |Cite
|
Sign up to set email alerts
|

“Opening” Art History: Exploring the Motivations and Practices of Faculty using Open Educational Resources in Lower-Level and General Education Art History Courses

Abstract: Although over the years the conceptual understanding of OER has improved, more insights are needed on faculty's discipline-specific practices with OER. This study explored the motivations and OER-related practices of faculty in lower-level and general education (GE) undergraduate art history courses in the United States. Using twelve in-depth interviews conducted over nineteen months, it investigated why, how and to what ends a diverse group of art historians use OER and related practices in their teaching. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…They also have more flexibility in what content is presented and how it is organized, they can include more recent content-even current events-and bring geographically distant or super local content into the classroom. 7 Many librarians have proposed affordability initiatives as a solution, acknowledging that teaching faculty are responsible for selecting and assigning course materials and librarians serve in a supporting role. 8 The authors have not identified any published studies that compare the benefits and challenges of OER and affordability initiatives, and this presentation seeks to fill that gap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also have more flexibility in what content is presented and how it is organized, they can include more recent content-even current events-and bring geographically distant or super local content into the classroom. 7 Many librarians have proposed affordability initiatives as a solution, acknowledging that teaching faculty are responsible for selecting and assigning course materials and librarians serve in a supporting role. 8 The authors have not identified any published studies that compare the benefits and challenges of OER and affordability initiatives, and this presentation seeks to fill that gap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies focus on the use of OERs to alleviate student financial pressure to achieve social inclusion and educational equity (Abramovich & McBride, 2018;Baker & Sibona, 2022). Other researchers investigate OER creation in specific disciplines, students' perceptions and learning outcomes, and instructors' motivations (Chtena, 2021;Kalaf-Hughes, 2021). However, limited research is available to describe and discuss OERbased course design and development in general education courses (Valentino & Hopkins, 2020).…”
Section: Introductionmentioning
confidence: 99%